Tissue engineered bone mimetics to study bone disorders ex vivo: Role of bioinspired materials. (April 2019) - Shih, Yuru Vernon; Varghese, Shyni
Abstract: Recent advances in materials development and tissue engineering has resulted in a substantial number of bioinspired materials that recapitulate cardinal features of bone extracellular matrix (ECM) such as dynamic inorganic and organic environment(s), hierarchical organization, and topographical features. Bone mimicking materials, as defined by its self-explanatory term, are developed based on the current understandings of the natural bone ECM during development, remodeling, and fracture repair. Compared to conventional plastic cultures, biomaterials that resemble some aspects of the native environment could elicit a more natural molecular and cellular response relevant to the bone tissue. Although current bioinspired materials are mainly developed to assist tissue repair or engineer bone tissues, such materials could nevertheless be applied to model various skeletal diseases in vitro . This review summarizes the use of bioinspired materials for bone tissue engineering, and their potential to model diseases of bone development and remodeling ex vivo . We largely focus on biomaterials, designed to re-create different aspects of the chemical and physical cues of native bone ECM. Employing these bone-inspired materials and tissue engineered bone surrogates to study bone diseases has tremendous potential and will provide a closer portrayal of disease progression and maintenance, both at the cellular and tissue level. We also briefly touch upon the application of patient-derived stem cells and introduce emerging technologies such as organ-on-chip in disease modeling. Faithful recapitulation of disease pathologies will not only offer novel insights into diseases, but also lead to enabling technologies for drug discovery and new approaches for cell-based therapies.